Humulene Diepoxides from the Australian Arid Zone Herb Dysphania: Assignment of Aged Hops Constituents. Issue 7 (21st January 2020) - Tan, Yuen Ping; Agnew‐Francis, Kylie A.; Hofmann, Julian; Savchenko, Andrei I.; Lafontaine, Scott R.; Boyle, Glen M.; Bernhardt, Paul V.; Fraser, James A.; Shellhammer, Thomas H.; Williams, Craig M.
Abstract: Dysphania is an abundant genus of plants, many of which are endemic to the Australian continent, occurring primarily in arid and temperate zones. Despite their prevalence, very few investigations into the phytochemistry of native Dysphania have been undertaken. Described herein, is the isolation and elucidation of two enantiomeric diastereomers of humulene diepoxide C from D. kalpari and D. rhadinostachya, of which unassigned diastereomers of humulene diepoxide C have been previously reported as components in beer brewed from aged hops. In addition, two (+)‐humulene diepoxiols (humulene diepoxiol C‐I and C‐II) were isolated from D. rhadinostachya . Analysis of Chinook hops oil confirmed the presence of both humulene diepoxide C‐I and C‐II as trace components, and in turn enabled GC‐MS peak assignment to the relative stereochemistry. Anticancer assays did not reveal any significant activity for the (+)‐humulene diepoxides. Antifungal assays showed good activity against a drug‐resistant strain of C. auris, with MIC50 values of 8.53 and 4.91 μm obtained for (+)‐humulene diepoxide C‐I and C‐II, respectively. Abstract : Eliciting from desert : The Australian desert plants Dysphania kalpari and D. rhadinostachya have yielded the first example of naturally occurring humuluene diepoxide C‐I and C‐II, which facilitated the assignment of the relative stereochemistry to these diepoxides that have origins in aged hops. Two new humulene diepoxiols were also isolated. The two diepoxides were observed to display good antifungal activity against a drug‐resistant C. auris strain.